Commuting and work-related accidents among employed Brazilians, National Survey of Health 2013 and 2019 - Deborah Carvalho Malta; Regina Tomie Ivata Bernal; Nádia Machado de Vasconcelos; Adalgisa Peixoto Ribeiro; Lêda Lúcia Couto de Vasconcelos; Elaine Leandro Machado (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the prevalence of work-related accidents, according to sociodemographic and occupational variables, in 2013 and 2019. Methods: Cross-sectional study using data from the National Survey of Health (PNS) 2013 and 2019. Typical work accidents (WA), commuting accidents (CA), and Total Work Accidents (TWA) were evaluated. Prevalence values and 95% confidence intervals (95%CI) of TWA in 2013 and 2019 were estimated according to the explanatory variables and for Federative Units and capitals. In 2019, the prevalence and 95%CI according to explanatory variables were estimated using prevalence ratios (PR), both crude and adjusted for sex and age group. Results: TWA prevalence decreased from 4.96% (95%CI 4.55-5.38) in 2013 to 4.13% (95%CI 3.80-4.46) in 2019. In 2013, the state of Pará prevailed in TWA, and the state of Mato Grosso in 2019. The prevalence of WA and CA in 2019 were: 2.64% (95%CI 2.37-2.91) and 1.60% (95%CI 1.40-1.80). In 2019, the prevalence for TWA were higher for men (PR: 1.92; 95%CI 1.62-2.27); in the 18-29 age group (PR: 2.71; 95%CI 1.99-3.68); people with elementary school and some high school (PR: 2.09; 95%CI 1.57-2.78); and Black individuals (PR: 1.43; 95%CI 1.12-1.84). People without formal employment contract had a lower prevalence of TWA (PR: 0.77; 95%CI 0.66-0.90). WA was higher in rural areas (PR: 1.32; 95%CI 1.09-1.60). Conclusion: There was a reduction in TWA between 2013 and 2019. Men, young people, Black people, and individuals with lower level of education, residents in rural areas had higher prevalence of WA in 2019, demonstrating a relationship between health-disease-accident processes.